2001
DOI: 10.1345/aph.1a052
|View full text |Cite
|
Sign up to set email alerts
|

Severe Pancytopenia Associated with Low-Dose Methotrexate Therapy for Rheumatoid Arthritis

Abstract: Severe pancytopenia associated with low-dose MTX therapy for rheumatoid arthritis is a potentially serious complication that may occur at any time during therapy. This adverse effect is more likely to occur in patients with renal impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 6 publications
1
16
0
1
Order By: Relevance
“…4 More significant ADRs and severe toxicities such as organ dysfunction (hepatic or renal failure), Stevens-Johnson syndrome (SJS), and severe mucositis can occur but at a much lower frequency. [4][5][6][7][8][9][10] The presence of documented risk factors including renal impairment, folate deficiency, advanced age, alcohol ingestion, hypoalbuminemia, drug-drug interactions, and drug dosing errors will increase the likelihood of a serious ADR. 4 In a recent retrospective review of methotrexate use in clinical practice, 50% of patients reported an adverse event while on therapy, with 32% of those being classified as "significant."…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 More significant ADRs and severe toxicities such as organ dysfunction (hepatic or renal failure), Stevens-Johnson syndrome (SJS), and severe mucositis can occur but at a much lower frequency. [4][5][6][7][8][9][10] The presence of documented risk factors including renal impairment, folate deficiency, advanced age, alcohol ingestion, hypoalbuminemia, drug-drug interactions, and drug dosing errors will increase the likelihood of a serious ADR. 4 In a recent retrospective review of methotrexate use in clinical practice, 50% of patients reported an adverse event while on therapy, with 32% of those being classified as "significant."…”
Section: Discussionmentioning
confidence: 99%
“…20 Pancytopenia has been observed in approximately 1.5% of patients taking oral low-dose methotrexate. 10 According to the classification reported by Day et al, 12 pancytopenia may be described as a type A (dosedependent) or type B (idiosyncratic) adverse reaction. Of the known risk factors that may contribute to methotrexate toxicity, renal impairment is recognized as the most common risk factor for low-dose methotrexateinduced pancytopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…İleri yaş, hipoalbüminemi, yüksek MCV değeri, dehidratasyon, kreatin klirensinin 50 mL/dk altında olması, enfeksiyon, ek ilaç kullanımı, günlük MTX alınması, düşük folik asit düzeyi, folik asit kullanılmaması pansitopeni gelişimi açısından risk faktörleridir (8)(9)(10)(11)(12). Olgularımızın 3'ünde de CrCL< 50 mL/dk iken, hipoalbüminemi, enfeksiyon, ek ilaç kullanımı, mukozit, folik asit almamayı içeren risk faktörleri de olup, sadece 1. olgumuzda MCV yüksekliği mevcuttu.…”
Section: Discussionunclassified
“…There are only several case reports, but the efficacy of methotrexate has not been proven in large controlled studies. There are few literature reports on pulmonary edema, sometimes even fatal, caused by methotrexate in low doses, and on pancytopenia that was observed with higher dose (106)(107)(108). The most important risk factor for methotrexate toxicity is impaired renal function.…”
Section: Methotrexatementioning
confidence: 99%